Edukasi Kader Kesehatan dan Ibu Balita Mengenai Stunting dan Makanan Sehat di Kecamatan Johar Baru - Sondang Ratnauli Sianturi; Monica Alfriyani; Steffi Cintya (Seminar Nasional Penelitian dan Abdimas, 2023)
Stunting is a chronic nutritional problem caused by a lack of nutrition in the long term. The problem of stunting occurs due to a lack of nutrition in the long term. The problem of stunting occurs due to a lack of understanding of mothers about nutrition in toddlers. The purpose of this activity is for cadres and mothers with toddlers to understand and explain stunting and nutrition for toddlers. Refreshing cadres and educating mothers with toddlers is one of the strategies in community empowerment. The implementation method consists of dialogue with the Primary Health Care, head of area, and mothers with toddlers, face-to-face refresher and education and leaflets distributed. This community service was attended by 12 cadres and 21 mothers with toddlers. Servants provide education to cadres and then cadres provide education to mothers with toddlers. The evaluation results found that 35,2% of mothers with toddlers coud understand and explain the differences in the meanings of stunting and malnutrition in toddlers, 64,7% could understand and explain the meaning of stunting and how to prevent it, 58,8% of mothers understood the 10 guidelines for balanced nutrition to provide adequate nutrition for toddlers and 64,7% of mothers understand how to prepare food for toddlers according to my plate guidelines. This activity shows an increase in the knowledge of cadres and mothers with toddlers regarding stunting and its management.